Bacteriological Study of Post-Operative Wound Infection and its Antibiograms - Apsha Shrestha; Stuti Koirala; Ashok Adhikari; Sweata Bhandari; Rajeshwar Reddy Kasarla; Laxmi Pathak (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Postoperative wound infections are a signiﬁcant complication of surgical procedures, which increases morbidity, mortality, prolonged hospital stay, and increased healthcare costs. The study was undertaken with an aim to investigate the etiological agents of postoperative wounds and their sensitivity to commonly used antibiotics. MATERIAL AND METHODS This study was a descriptive cross-sectional prospective study, carried out at Universal College Of Medical Sciences-Teaching Hospital, Bhairahawa, Nepal, on 100 postoperatively wounded infected cases, during April 2023 – August 2023, Non Probability sampling method (Purposive sampling) was used, and specimens were collected by sterile cotton swabs and pus was aspirated with a sterile needle and syringe and processed using standard bacteriological techniques. Antibiotic sensitivity test was conducted by disc diffusion (Kirby-Bauer) method. RESULTS Postoperative wound infections caused by Gram negative bacilli were more frequent and predominant pathogens involved were Pseudomonas aeruginosa, followed by Klebsiella spp and Enterobacter aerogenes. Among Gram positive bacteria Staphylococcus aureus was predominant. Gram positive cocci were highly sensitive to Ampicillin, and Gram negative bacilli were highly sensitive to Ceftazidime, Gentamicin, and Amikacin. Coagulase negative staphylococci were resistant to all drugs tested. CONCLUSION Pseudomonas aeruginosa was the commonest etiological agent for postoperative wound infections. Gram positive cocci and E.coli were highly sensitive to Ampicillin and Gram negative bacilli were highly sensitive to Ceftazidime, Gentamicin, Amikacin. Staphylococcus aureus was resistant to vancomycin and Teicoplanin and coagulase staphylococci were resistant to all drugs tested. Gram negative bacilli were resistant to Polymyxin B and Tigecycline. Increasing resistance to commonly used antibiotics warrants the judicious use of antibiotics and establishment of antibiotic policy in the hospital.